Syntactic complexity of research article part-genres: Differences between emerging and expert international publication writers. (April 2021) - Yin, Shuhui; Gao, Yuan; Lu, Xiaofei
Abstract: This study investigated the differences between emerging and expert international publication (IP) writers' engagement with syntactic complexity in seven research article (RA) part-genres. Our data consisted of 30 RAs published in an emerging international journal authored by Chinese applied linguists with no prior English language publication and 30 RAs published in a top international journal authored by applied linguists with multiple prior publications in prominent international journals. Our analysis using 14 measures covering multiple dimensions of syntactic complexity revealed significant differences between emerging and expert IP writers in terms of the syntactic complexity of different RA part-genres and the patterns of cross-part-genre syntactic complexity variation. Our findings contribute to a better understanding of the syntactic complexity of second language (L2) English for Research Publication Purposes (ERPP) writing and have useful implications for genre-based L2 ERPP writing pedagogy.